Comparative analysis of YAG laser vitreolysis and posterior vitrectomy in diabetic hemophthalmus - E. M. Gasimov; N. I. Aliyeva (Oftalʹmologiâ, 2014)
Purpose: To conduct a comparative analysis of YAG laser vitreolysis and posterior vitrectomy in diabetic hemophthalmus.Materials and Methods. The study included 96 patients (106 eyes) aged 43‑72, 57 women and 39 men, with PDR complicated by hemophthalmus. Of them, there were 57 women and 39 men. All the patients have been divided into 2 groups. Group I consisted of 61 patients (67 eyes) with YAG laser vitreolysis. 35 patients (39 eyes) in group II had a retrospective analysis of the results of surgical vitrectomy for PDR complicated by hemophthalmus. There were 10 men and 25 women with the average age of 59,4±9,2. All the patients were examined prior to the treatment and in the dynamics on the 10th day; 1, 3, 6, 9 and 12 months. Examination methods: visometry, tonometry, biomicroscopy, ophthalmoscopy and ultrasound methods (B-scan and quantitative sonography). Quantitative sonography was performed to determine the density of the hemophthalmus.Results. Visual acuity 1st group patients before treatment in 1st subgroup was 0,169±0,05, in 2nd subgroup — 0,05±0,007, in 3rd subgroup — 0,012±0,003, the subgroups have to be reflected in the previous section, in group II — 0,039±0,012 (Fig. 6). Visual acuity was significantly higher in subgroup 1 compared to 2 — (р<0,005), compared to 3 (р<0,001) and to a comparison group (р<0,005). In subgroup 2 it was significantly higher compared to 3 (p <0.001), there was no significant difference  ith the group II (p> 0.05). Compared with the group II visual acuity in subgroup 3 was significantly lower (р<0,05). Period of hemophthalmia in 1st subgroup was 1,71±0,62 months, in 2nd subgroup — 2,77±1,48, in the 3rd subgroup — 2,64±1,32 months, in group II — 2,32±1,05 months.Vitreous surgery remains the treatment of choice, but the complications after it are observed in 15‑46 % of cases, the recovery of visual function is only in 45 % of cases.Conclusions. 1. Vitrectomy being the gold standard and cardinal solution in the treatment of diabetic hemophthalmus has a number of complications and requires expectant tactics and satisfactory somatic status of the patients. 2. Use of YAG laser vitreolysis at early stages, the possibility of repeated surgeries, a favorable safety profile and a narrow range of complications make it possible to recommend this method to treat patients with DR complicated by hemophthalmus. 3. Given that vitrectomy is performed at later stages of the hemophthalmus the YAG laser vitreolysis can be used at early stages as an alternative method to treat diabetic retinopathy complicated by recidivous hemophthalmus.